2019
DOI: 10.1101/568543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA sequence differences are determinants of meiotic recombination outcome

Abstract: PreambleDue to a mistake during analysis of a batch of Sanger sequencing reactions for Supplementary Figure S1, we erroneously stated that we found evidence for intragenic crossovers. We now show that intragenic crossovers are less likely than we initially thought. We sincerely apologize for our mishap and any inconvenience it might have caused. However, this does not affect the main conclusions of our paper, just how some of our results are interpreted. This new manuscript version has been amended accordingly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In our study, we showed that the number of DMC1 foci decreases under heat stress (Fig. 3), which supports the notion that DMC1 is a potential target of high temperature (Brown et al, 2019). The expression of DMC1 under heat stress is not significantly changed, but RAD51 is lowered (Fig.…”
Section: Dmc1-dependent Mr Is a Potential Target Of Heat Stresssupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, we showed that the number of DMC1 foci decreases under heat stress (Fig. 3), which supports the notion that DMC1 is a potential target of high temperature (Brown et al, 2019). The expression of DMC1 under heat stress is not significantly changed, but RAD51 is lowered (Fig.…”
Section: Dmc1-dependent Mr Is a Potential Target Of Heat Stresssupporting
confidence: 85%
“…Moderate elevation of temperature promotes MR in Arabidopsis via enhanced activation of type-I CO formation pathway but not by influencing DSB formation (Lloyd et al, 2018;Modliszewski et al, 2018). Similarly, in Schizosaccharomyces pombe, MR rate is moderately changed without alteration in DSB formation under temperatures within fertile range from 16 to 33°C (Brown et al, 2019). It thus is possible that DSB catalyzation system has a threshold to increase of environmental temperature, below which the system functions normally and generates DSBs.…”
Section: Discussionmentioning
confidence: 99%